2023
DOI: 10.1039/d2nr05786g
|View full text |Cite
|
Sign up to set email alerts
|

Water-based 2-dimensional anatase TiO2 inks for printed diodes and transistors

Abstract: 2-Dimensional (2D) materials are attracting strong interest in printed electronics because of their unique properties and easy processability, enabling to fabricate devices with low cost and mass scalable methods, such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…We also found that the parallel conductance of the albumen dielectric is up to one order of magnitude higher than that expected for an ideal solid-state capacitor. These two observations are compatible with the presence of ionic current within the albumen, and thus the formation of an electric double layer, typical of capacitors based on ionic materials 41 , 42 . This mechanism would explain the observed high mobility in the albumen-based MoS 2 transistor as it has been reported that ionic gating can improve the carrier mobility in MoS 2 reaching up to ~100 cm 2 V −1 s −1 at room temperature, inducing ionic gating rather than solid-state electric field effect 43 45 .…”
Section: Resultssupporting
confidence: 79%
“…We also found that the parallel conductance of the albumen dielectric is up to one order of magnitude higher than that expected for an ideal solid-state capacitor. These two observations are compatible with the presence of ionic current within the albumen, and thus the formation of an electric double layer, typical of capacitors based on ionic materials 41 , 42 . This mechanism would explain the observed high mobility in the albumen-based MoS 2 transistor as it has been reported that ionic gating can improve the carrier mobility in MoS 2 reaching up to ~100 cm 2 V −1 s −1 at room temperature, inducing ionic gating rather than solid-state electric field effect 43 45 .…”
Section: Resultssupporting
confidence: 79%
“…2D materials are very attractive for the fabrication of printed memristors as they can be easily processed into inkjet printable formulations and used to fabricate the full device. 5–13 However, very few works have reported fully printed 2DMs-based memristors: most of the literature is based on the use of non-scalable deposition methods such as spin coating or drop casting. In particular, only 3 works have reported printed memristors made of 2DMs, 14–16 while few works have also reported printed devices made with other types of nanomaterials 17–28 (see ESI,† Tables SI and SII).…”
Section: Introductionmentioning
confidence: 99%